Recurrent hemolytic uremic syndrome caused by gene mutation: a case report - Baek Sup Shin; Yo Han Ahn; Hee Gyung Kang (Korean Society of Pediatric Nephrology, 2022)
Atypical hemolytic uremic syndrome (aHUS) is a rare disease characterized by microangiopathic hemolytic anemia, thrombocytopenia, and acute kidney injury without any association with preceding diarrhea. Dysregulation of the complement system is the most common cause of aHUS, and monoclonal humanized anti-C5 antibodies are now recommended as the first-line treatment for aHUS. However, if the complement pathway is not the cause of aHUS, C5 inhibitors are ineffective. In this study, we report the second reported case of aHUS caused by DGKE mutations in Republic of Korea. The patient was an 11-month-old infant who presented with prodromal diarrhea similar to typical HUS, self-remitted with conservative management unlike complement-mediated aHUS but recurred with fever. While infantile aHUS often implies genetic dysregulation of the complement system, other rare genetic causes, such as DGKE mutation, need to be considered before deciding long-term treatment with C5 inhibitors.